Semiconductive Amine-Functionalized Co(II)-MOF for Visible-Light-Driven Hydrogen Evolution and CO2 Reduction - Liao, Wei-Ming; Zhang, Jian-Hua; Wang, Zheng; Lu, Yu-Lin; Yin, Shao-Yun; Wang, Hai-Ping; Fan, Ya-Nan; Pan, Mei; Su, Cheng-Yong (Inorganic chemistry, 2018)
A Co-MOF, [Co3(HL)2·4DMF·4H2O] was simply synthesized through a one-pot solvothermal method. With the semiconductor nature, its band gap was determined to be 2.95 eV by the Kubelka–Munk method. It is the first trinuclear Co-MOF employed for photocatalytic hydrogen evolution and CO2 reduction with cobalt–oxygen clusters as catalytic nodes. Hydrogen evolution experiments indicated the activity was related to the photosensitizer, TEOA, solvents, and size of catalyst. After optimization, the best activity of H2 production was 1102 μmol/(g h) when catalyst was ground and then soaked in photosensitizer solution before photoreaction. To display the integrated design of Co-MOF, we used no additional photosensitizer and cocatalyst in the CO2 reduction system. When −NH2 was used for light absorption and a Co–O cluster was used as catalyst, Co-MOF exhibited an activity of 456.0 μmol/(g h). The photocatalytic mechanisms for hydrogen evolution and CO2 reduction were also proposed.